The Use of Complex Sentence in Selected Play: As a Stylistic Study - Yaseen Mohammed Ridha Hussein (مجلة الباحث, 2025)
This paper tackles the investigation of the use of complex sentences in Stoppard’s play “Jumpers” and the types of sentences. It aims to examine how the complex sentences are used in his play “Jumpers,” to investigate the reasons behind the use of such kinds of sentences, and in order to find out whether this structure is evenly employed or whether it is an idiosyncrasy of one of the writers. This study will also review the structure and type of sentences. In the play “Jumpers,” the use of complex sentences depends on the type of character. The study showed that the complex sentences rise according to the importance of the character in the play. The investigation arrived at several facts regarding the use of complex sentences in the play, which is mentioned later on in the conclusion of the study.